Bamboo as a Building Materials - sumadi, khairul afham; Ayop, Sallehuddin Shah (Recent Trends in Civil Engineering and Built Environment, 2022)
This study was conducted to perform an in-depth study on the mechanical properties, behavior and the effectiveness of bamboo as steel replacement in reinforced concrete. The aim of this paper is to determine the ultimate tensile strength of bamboo strip through an understanding of tensile test curve and the flexural strength and the capacity of concrete beam reinforced with bamboo. There are two bamboo strips size of (10×16mm) and three sample consist of unreinforced and two bamboo reinforced concrete beam with different dimension will be tested under tensile test and three-point bending test. The average data for max tensile force, ultimate tensile strength and young modulus are 24.45 kN, 152.81 MPa and 11538.36 MPa respectively while the three-point bending test shows the control concrete beam has 35.60 kN of ultimate load with flexural strength of 7.56 N/mm^2, 10×10mm BRC beam has 42.87 kN of ultimate load with 9.117.56 N/mm^2 of flexural strength and 10×16mm BRC beam has 37.72 kN of ultimate load with 8.01 N/mm^2 of flexural strength. The tensile result shows that bamboo undergoes brittle failure where it breaks sharply without through plastic deformation. The experimental result of flexural modulus of three-point bending test displays the sample 1 has the highest value followed by sample 3 and sample 2. This analysis proved that the sample 1 is stiffer and has low ability to bend during the load action.